Infections caused by clonal spread of metallo-beta-lactamase-producing Enterobacter cloacae complex isolates at a southern Taiwan hospital - Cong-Tat Cia; Shu-Li Su; Pei-Fang Tsai; Yu-Cheng Su; Nan-Yao Lee; Wen-Chien Ko; Po-Lin Chen (Microbiology Spectrum, 2025)
ABSTRACT Carbapenem-resistant Enterobacter cloacae complex (ECC) has become a clinically important pathogen with increased incidence worldwide in recent years. In Taiwan, IMP-8 accounted for most carbapenemase produced by ECC in earlier studies. Clinical ECC isolates resistant to ertapenem, imipenem, and meropenem at the study hospital between 2014 and 2022 were collected at a medical center in southern Taiwan. The isolates were subjected to multilocus sequence typing, species identification by hsp60 sequencing, polymerase chain reaction detection of beta-lactamase genes, antimicrobial susceptibility tests, and whole genome sequencing analysis. Fifty-four ECC isolates causing infections were included. Bloodstream (20 episodes, 37.0%) and lower respiratory tract infections (14, 25.9%) were the common infection types. The crude in-hospital mortality was 51.8%. Carbapenemase genes were detected among 90.7% of the isolates, and blaIMP-8 remained to be the most common gene. The amikacin and colistin resistance rates were lower than 20%, while other agents were less active in vitro. Infections caused by ECC with extensive carbapenem resistance herald a poor prognosis and have limited treatment options. Clonal spread of blaNDM-1 harboring E. hormaechei subsp. xiangfangensis ST171 and blaVIM-1 harboring E. hormaechei subsp. hoffmannii ST78, which have not been reported in Taiwan, was responsible for the increased incidence of ECC with complete resistance to tested carbapenems since 2019.IMPORTANCEThis study reported the increase of carbapenemase-producing Enterobacter cloacae complex (ECC) isolates at a medical center in southern Taiwan during 2014 and 2022. The emergence of NDM-1-producing E. hormaechei subsp. xiangfangensis ST171 and VIM-1-producing E. hormaechei subsp. hoffmannii ST78, contrary to widely reported IMP-8-producing carbapenem-resistant E. cloacae complex, accounts for the increased incidence of health care-associated infections with few remaining treatment options and poor clinical outcomes. Our findings highlighted the changing antimicrobial resistance of carbapenem resistance among Enterobacterales, leading to clinical difficulties in Taiwan.